38.1k views
5 votes
I don’t understand how to solve itCan you solve elimination using addition and subtraction equations?

I don’t understand how to solve itCan you solve elimination using addition and subtraction-example-1

1 Answer

7 votes

Given the system of equations:


\begin{gathered} x+4y=11\rightarrow(1) \\ x-6y=11\rightarrow(2) \end{gathered}

We will solve the system by the elimination method

Subtract equation (2) from equation (1)

So,


\begin{gathered} (x+4y)-(x-6y)=11-11 \\ x+4y-x+6y=0 \\ (x-x)+(4y+6y)=0 \\ 10y=0 \\ y=0 \end{gathered}

Substitute with (y) into equation (1) to find (x)


\begin{gathered} x+4\cdot0=11 \\ x=11 \end{gathered}

So, the answer will be:


\begin{gathered} x=11 \\ y=0 \\ (x,y)=(11,0) \end{gathered}

User Billa
by
6.2k points